Multiple Photoluminescence from Pyrene‐Fused Hexaarylbenzenes with Aggregation‐Enhanced Emission Features. Issue 2 (15th January 2018) - Wang, Chuan‐Zeng; Noda, Yuki; Wu, Chong; Feng, Xing; Venkatesan, Perumal; Cong, Hang; Elsegood, Mark R. J.; Warwick, Thomas G.; Teat, Simon J.; Redshaw, Carl; Yamato, Takehiko
Abstract: Multiple photoluminescence, which included monomer emission, excimer emission, and charge‐transfer emission processes, has been observed from new pyrene‐fused hexaarylbenzene (HAB) compounds, which were synthesized in high yields through a Diels–Alder reaction between bis(2‐ tert ‐butylpyren‐6‐yl)acetylene and tetraphenylcyclopentadienone. Although the differentiation between the two molecules only arose from the geometrical position of one of the pyrenes, the NMR spectra, crystal packing, and physicochemical properties of these pyrene‐based HAB hybrids were distinctly different in both the solution and aggregate states. X‐ray diffraction analysis clearly indicated that the pyrene moieties adopted different crystal packing arrangements in the crystalline state that could induce a multiple‐photoluminescence phenomenon. Abstract : Checking into reHAB : Multiple photoluminescence, which included monomer emission, excimer emission, and charge‐transfer emission processes, has been observed from new pyrene‐fused hexaarylbenzenes (HABs). X‐ray diffraction analysis clearly indicated that the pyrene moieties adopted different crystal packing arrangements in the crystalline state that could induce a multiple‐photoluminescence phenomenon.